Terminator : dark fate [videorecording (Blu-Ray)] - Hamilton, Linda, 1956-; Schwarzenegger, Arnold; Davis, Mackenzie; Reyes, Natalia, 1987- (Paramount Home Entertainment, 2020)
More than two decades have passed since Sarah Connor prevented Judgment Day, and re-wrote the fate of the human race. Dani Ramos is living a simple life with her brother and father when a deadly new Terminator, a Rev-9, travels back through time to kill her. In order to survive, she joins forces with Grace, an enhanced super-soldier from the future, and a battle-hardened Sarah Connor. As the Rev-9 destroys everything in its path, the three are led to a T-800 from Sarah's past as their last hope.